Review of the indexes to assess the ecological quality of coralligenous reefs: towards a unified approach - Di Camillo, Cristina Gioia; Ponti, Massimo; Storari, Annalisa; Scarpa, Clarissa; Roveta, Camilla; Pulido Mantas, Torcuato; Coppari, Martina; Cerrano, Carlo (Frontiers in Marine Science, 2023)
There is an urgent need to better understand the stressors, namely heatwaves, changes in thermohaline circulation and mucilage events, that are rapidly re-shaping bioconstructions, such as coralligenous assemblages. This calls for increased monitoring efforts in these invaluable habitats that will improve our understanding of the resistance and resilience of bioconstructions. Since 2009, 16 indexes have been designed to assess the ecological quality of Mediterranean coralligenous reefs. The main objective of this work is to propose a framework to support the development of a shared, cost-effective, and practical index to assess the status of the coralligenous biocenosis. To achieve this, studies conceiving these 16 indexes were reviewed: comparing their objectives, metrics, and applied methodologies. A standardized nomenclature of anthropogenic pressures is supplied, using, when possible, definitions from the European Habitat Directive, Marine Strategy Framework Directive and Water Framework Directive. Additionally, given the unprecedented climatic conditions, we highlight that a common index should give particular attention to the response of the coralligenous to thermal stress and mucilage. A list of priority anthropogenic pressures/environmental stressors and relative indicators and metrics are suggested. This review stresses the urgency to align the methodologies at basin scale and highlights the pros and cons of the preexisting indexes that must be considered in the design of a new, shared procedure to evaluate the status of coralligenous assemblages.